(untitled) (Italiano LinguaDue, 2025)
Il lavoro, nato in seno al progetto PRIN PNRR 2022 “Dizionario dell’italiano accademico: forme e funzioni testuali (DIA)”, ha l’obiettivo di verificare l’uso e la frequenza del lessico “accademico” in un campione di manuali didattici destinati alla scuola secondaria di secondo grado. Dopo una premessa metodologica e una ricognizione sulle problematiche legate all’apprendimento del lessico nella scuola, sono forniti i dati emersi dalla ricerca ed enucleate alcune osservazioni complessive sull’indagine svolta. Academic Italian in school textbooks: a sample survey The work, which originated within the PRIN PNRR 2022 project “Dictionary of Academic Italian: Forms and Textual Functions (DIA)”, aims to examine the use and frequency of “academic” vocabulary in a sample of textbooks intended for secondary school education. After a methodological introduction and a review of issues related to vocabulary learning in schools, the data obtained from the research will be presented, along with some overall observations on the study conducted.